Gleeok’s Fire-breathing: Triple Flares of AT 2021aeuk within Five Years from the Active Galaxy SDSS J161259.83+421940.3 - Dong-Wei Bao; Wei-Jian Guo; Zhi-Xiang Zhang; Cheng Cheng; Zhu-Heng Yao; Yan-Rong Li; Ye-Fei Yuan; Sui-Jian Xue; Jian-Min Wang; Chao-Wei Tsai; Hu Zou; Yong-Jie Chen; et al. (The Astrophysical Journal)
We present a noteworthy transient AT 2021aeuk exhibiting three distinct optical flares between 2018 and 2023. It is hosted in a radio-loud narrow-line Seyfert 1 galaxy, with an optical image showing a minor tidal morphology and a red mid-infrared color ( W 1 − W 2 = 1.1). Flares II and III exhibit rapid rises, and long-term decays (≳1000 days) with recurring after-peak bumps. The g − r color after subtracting the reference magnitude exhibited a rapid drop and recovery during Flare II, followed by a minor after-peak evolution in blue colors. We applied a canonical tidal disruption event (TDE) fitting on the light curves, which gives a decay index p of $-{2.99}_{-0.14}^{+0.13}$ for Flare II and $-{1.61}_{-0.65}^{+0.34}$ for Flare III. The blackbody fitting shows lower temperatures (∼10 ^3.8 K) with minor after-peak evolution. The blackbody radius (≳10 ^16 cm) and luminosity (∼10 ^45 erg s ^−1 ) are larger than the typical TDE sample’s. The time lag (in rest frame) between the ZTF g and r bands ( ${τ }_{g,r}={3.4}_{-0.9}^{+1.0}$ days) significantly exceeds the prediction from the standard accretion disk. Pre-burst spectra reveal prominent Bowen fluorescence lines, indicating a vigorous or potentially long-lasting process that enriches the local metallicity. Additionally, we derived black hole masses of $logM_{\bullet }={7.09}_{-0.31}^{+0.18}\ M_{\odot }$ and $logM_{\bullet }={7.52}_{-0.10}^{+0.08}\ M_{\odot }$ using H β and H α emission lines. The variation and recurring features of AT 2021aeuk are not likely induced by the radio-beaming effect or Type II superluminous supernova; however, we cannot rule out the possibility of TDE or enhanced active galactic nuclei accretion process. The unusually high occurrence of three flares within 5 yr may also induced by the complex local environment.